The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1227/01.neu.0000166661.96546.33
|View full text |Cite
|
Sign up to set email alerts
|

Herniation Secondary to Critical Postcraniotomy Cerebrospinal Fluid Hypovolemia

Abstract: Severe cerebrospinal fluid hypovolemia after craniotomy may produce a dramatic herniation syndrome that is completely reversed by the Trendelenburg position. Brain sag should be included in the differential diagnosis for acute postoperative clinical deterioration in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 13 publications
2
60
0
2
Order By: Relevance
“…5,6,42,72,73 With a large skull defect, a lumbar puncture exacerbates the negative pressure gradient between the atmosphere and the cranium. 93 Based on this, we have adopted a high threshold for performing lumbar puncture in patients with a decompressive craniectomy.…”
Section: Postoperative Complications Within 30 Daysmentioning
confidence: 99%
“…5,6,42,72,73 With a large skull defect, a lumbar puncture exacerbates the negative pressure gradient between the atmosphere and the cranium. 93 Based on this, we have adopted a high threshold for performing lumbar puncture in patients with a decompressive craniectomy.…”
Section: Postoperative Complications Within 30 Daysmentioning
confidence: 99%
“…Since Yamamura et al 15) reported in 1977, the syndrome of the sinking skin flap with neurological deterioration has been reported in the literature 2,5,7,8,11,12) . Many investigators have sought to explain the pathophysiology of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 4,5) suggested that severe CSF hypovolemia after craniotomy may produce a dramatic herniation syndrome that is completely reversed by the Trendelenberg position. Also, it was reported that intrathecal saline infusion reverses impending transtentorial herniation in patient with decline of mental status due to intracranial hypotnesion 1) .…”
Section: Discussionmentioning
confidence: 99%
“…3 The Trendelenburg position reversed the symptoms in all patients. Thalamus/basal ganglia hypodensities on CT scan have neither been described in these patients nor in various case reports, [12][13][14][15][16][17] whereas global cerebral edema on admission CT scan and a longer operative time were identified as risk factors for the development of symptomatic CSF hypovolemia.…”
mentioning
confidence: 83%
“…1 MR imaging signs include thickening and enhancement of the dura after contrast administration, subdural fluid collections, sagging of the brain, engorgement of venous structures with dilation of the intracranial dural sinuses and spinal epidural plexuses, and enlargement of the pituitary gland. [1][2][3][4][5][6] CSF loss is suggested as a possible pathogenetic mechanism, though the exact location of CSF loss often remains undetected. 7,8 According to the Monro-Kellie doctrine, in a closed compartment (as within the skull) the volume loss of 1 compartment-CSF in this disease entity-is compensated by an increase of the volume in the other ones.…”
mentioning
confidence: 99%